Hukum Pidana dan Konflik Agama: Menganalisis Kasus Penistaan Agama dan Dampak Sosialnya - Fahrudin, Ahmad Yogi; Ardiansyah; Ajie, Bintang Wicaksono (HUMANIORUM, 2023)
This research, entitled "Criminal Law and Religious Conflict: Analyzing Religious Blasphemy Cases and Their Social Impact," explores the interaction between criminal law and religious conflict in Indonesia, with a focus on religious blasphemy cases and their implications for freedom of religion and expression. Using a qualitative approach, this research collects data through the analysis of legal documents, judicial decisions, news reports, and other related sources. This research identifies that Indonesia's legal framework, including the Criminal Code and the ITE Law, provides a strong basis for protecting religious values while safeguarding human rights. However, there are challenges in the interpretation and application of the law that give rise to uncertainty and potential injustice. The analysis found that court decisions in religious blasphemy cases have a significant impact on public perceptions of justice and religious plurality. Careful decisions by courts often demonstrate the state's commitment to maintaining social harmony, but on the other hand, they can also trigger tensions and negative reactions. Therefore, this research suggests the need for a holistic and sustainable approach, involving education and interfaith dialogue, to minimize religious-based conflict. This research concludes that legal sanctions are not always effective in preventing or remediating acts of religious blasphemy. As an alternative, strategies that include education and interfaith dialogue, as well as rehabilitative and restorative approaches to perpetrators, are recommended to achieve balanced justice and strengthen social harmony. This research provides important insights into how criminal law and religious conflict are interrelated, as well as their impact on social life and justice in Indonesia.